Antioxidative, anticancer, and antibacterial activities of a nanogel containing Mentha spicata L. essential oil and electrospun nanofibers of polycaprolactone-hydroxypropyl methylcellulose - Fatemeh Rasti; Yaser Yousefpoor; Abbas Abdollahi; Mojdeh Safari; Ghazaal Roozitalab; Mahmoud Osanloo (BMC, 2022)
Abstract Background As the largest organ, the skin has been frequently affected by trauma, chemical materials, toxins, bacterial pathogens, and free radicals. Recently, many attempts have been made to develop natural nanogels that, besides hydrating the skin, could also be used as antioxidant or antibacterial agents. Methods In this study, the chemical composition of the Mentha spicata essential oil was first investigated using GC-MS analysis. Its nanoemulsion-based nanogel was then investigated; successful loading of the essential oil in the nanogel was confirmed using FTIR analysis. Besides, nanogel's antioxidative, anticancer, and antibacterial activities were investigated. Results Carvone (37.1%), limonene (28.5%), borneol (3.9%), β-pinene (3.3%), and pulegone (3.3%) were identified as five major compounds in the essential oil. By adding carboxymethylcellulose (3.5% w/v) to the optimal nanoemulsion containing the essential oil (droplet size of 196 ± 8 nm), it was gelified. The viscosity was fully fitted with a common non-Newtonian viscosity regression, the Carreau-Yasuda model. The antioxidant effect of the nanogel was significantly more potent than the essential oil (P < 0.001) at all examined concentrations (62.5-1000 µg/mL). Furthermore, the potency of the nanogel with an IC50 value of 55.0 µg/mL was substantially more (P < 0.001) than the essential oil (997.4 µg/mL). Also, the growth of Staphylococcus aureus and Escherichia coli after treatment with 1000 µg/mL nanogel was about 50% decreased compared to the control group. Besides, the prepared electrospun polycaprolactone-hydroxypropyl methylcellulose nanofibers mat with no cytotoxic, antioxidant, or antibacterial effects was proposed as lesion dressing after treatment with the nanogel. High potency, natural ingredients, and straightforward preparation are advantages of the prepared nanogel. Therefore, it could be considered for further consideration in vivo studies.